Pandangan Islam Terhadap Wanita Bekerja - Ali, Fatimah (Jurnal Usuluddin, 1996)
This article attempts to look into the opinions of ulama’ about women or wives who are having a career outside their home- Their opinions are supported by Qur’anic verses, hadith, observation and experiments. This article also discusses the legal judgement of ulama’ on women who work away from their home, the factors which influence this phenomenon and etcetra. Besides, this article forwards the writer’s opinion of today working teenage girls and housewives.